Insulin resistance accounts for metabolic syndrome‐related alterations in brain structure: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Lu, Ran; Aziz, N Ahmad; Diers, Kersten; Stoecker, Tony; Reuter, Martin; Breteler, Monique MB
Abstract: Background: Metabolic syndrome (MetS) is a major public health burden worldwide and associated with brain abnormalities. Although insulin resistance is considered a pivotal feature of MetS, its role in the pathogenesis of MetS‐related brain alterations in the general population is unclear. Therefore, we aimed to 1) assess the relation of metabolic syndrome (MetS) and insulin resistance with brain structure, and 2) determine to what extent the effects of MetS on brain structure are due to insulin resistance. Methods: We used cross‐sectional data from 973 participants (43.4% male, mean age 52.5 years) of the Rhineland Study, an ongoing population‐based cohort study. MetS was defined in accordance with the revised criteria of the National Cholesterol Education Program Adult Treatment Panel III. Insulin resistance was assessed through fasting serum insulin and the homeostatic model assessment of insulin resistance. Cortical reconstruction and volumetric segmentation were obtained from high‐resolution brain images at 3 Tesla. The relation between metabolic measures and brain structural features was assessed through (generalized) linear models. Results: MetS and insulin resistance were both associated with smaller cortical gray matter volume and mean cortical thickness, but not with white matter or subcortical gray matter volume. Vertex‐based brain morphometry showed that MetS and insulin resistance were related to brain structure in a similar spatial pattern, with the largest effect sizes observed in the precentral cortex, transverse and superior temporal cortex, and the cuneus and its neighboring regions. There was no independent effect of MetS on cortical gray matter when additionally adjusted for insulin resistance. Conclusion: MetS and insulin resistance are associated with cortical gray matter thinning, especially in regions involved in motor regulation and auditory and visual processing, with insulin resistance largely accounting for MetS‐related changes in brain structure.